Obcy, czyli wróg – o sposobach prezentowania Niemców w powojennych programach nauczania języka polskiego - Kaniewski, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
In this text, I show how Polish–German relations were depicted in the educational discourse. I analyse post-war Polish programmes and curricula, paying special attention to those from the second half of the 1940s, as they are the clearest example of how the way that the image of our Western neighbour was presented fit the ideological line imposed by the government at the time. I am interested in the then-current selection of topics and the prescribed reading, as well as in the accompanying didactical commentary which, in the first few curricula, takes the form of ideologised briefings. I also underline the way that schools were intertwined in the legitimation processes, which benefited the government’s interests. Of special interest to me is the identity project forming part of education, especially the model of Polish patriotism which was built over the figure of “the enemy” – which is also apparent in today’s form of patriotism.